A low-power variable-gain amplifier with improved linearity : analysis and design - Chen, Zhiming (2013)
A low-power variable-gain amplifier (VGA) based on transconductance (gm)-ratioed amplification is analyzed and designed with improved linearity. The VGA has the merits of continuous gain tuning, low power consumption and small chip area. However, the linearity performance of the gm-ratioed amplifier is usually poor. We analyze distortion in gm-ratioed amplifiers and propose to improve the output linearity by applying load degeneration technique. It is found that theoretically the output linearity can be improved by 8.5 dB at the same power consumption. We also analyze gain, bandwidth and noise performance of the gm-ratioed amplifiers. Two VGAs based on gm-ratioed amplification are designed and fabricated in a 0.18-μm CMOS process-one with load degeneration only and the other with both input and load degeneration. The VGA with load degeneration only achieves gain of -20 to 41 dB, bandwidth of 121 to 211 MHz, and input and output P1dB up to - 17 dBm and 0.65 dBm, respectively. The VGA with both input and load degeneration achieves gain of -37 to 28 dB, bandwidth of 76 to 809 MHz, and input and output P1dB up to - 2.63 dBm and 2.29 dBm, respectively. The two VGAs consume a similar amount of power, which is about 3 to 5 mW from a 1.8-V supply. For the same bias condition, the proposed load degeneration improves the output linearity by more than 15 dB.